DETERMINATION OF AFTER-RIPENING PERIOD AND HORMONAL RESPONSE OF OROBANCHE SOLMSII C.D. CLARKE SEEDS - Bista, A.; Khattri, G. B.; Acharya, B. D.; Srivastava, S. C. (Ecoprint: An International Journal of Ecology, 2004)
To find out the ability of Orobanche seeds to germinate immediately after seed set, seeds were germinated periodically at an interval of three months for one year in GR24. Some Orobanche seeds were capable of germination immediately after seed set but most required about nine months as after ripening or incubation period to be able to germinate. The phenomenon of after ripening in Orobanche seeds could be taken as an ecological measure to dormant over following unfavorable wet summer season. The growth hormone studies on Orobanche seed germination have shown that GA3 at a concentration of 100 ppm substantially enhanced seed germination when applied during pre-conditioning period. NAA showed some stimulatory effect at 0.5 - 1.0 ppm when applied during post-conditioning period but the hormone if applied during pre-conditioning period inhibited the germination. Kinetin failed to stimulate the germination at all the concentrations tested. Key words: Germination, root-parasite, hormone. Ecoprint Vol.11(1) 2004.